Postgraduate Students Skills in Scientific and Methodological Writing for Master Thesis - Abdul-Fattah, Ruaa Abdul Razzaq (Al-Adab Journal, 2021)
The study Aimed at Revealing That Scientific writing skills To Master thesis For Graduate Students. No Doubt That the Skill of Scientific Writing Academy Its Language Skill, for university Professors and Graduate Student Whom Scientific Research and Scientific production Constitute Distinguishing Mark in Their personalities And Standard to Be Judged by Them or by them. Which Prompted the Researcher To search for the most Important Skills That Contributed to raise the level Of Scientific Writing for Graduate Student. The Researcher Prepared a Questionnaire Consisting of 35 Item Distributed on four Axes: Which Are research Skills, Ideas Skill, Continuation Skills, Style Skills, Documentation Skill After Making Sure of Its Validity and Reliability. It Was Applied to the Graduate Students of The Department of Educational and Psychological Sciences, Who Numbered in Total (24) Meal, (43) Female Statistical Means ,chi-Square, Weight Means And Pearson Coefficient ,To reveal The Results Of Her Search The Results Saved That (16) Items Represents Achieved Aspects And(14)Item Represents Not Achieved Aspect .The Results Revealed That The Highest Skill Axes In Terms Of Weighted Average And Percentage Weight Are Skill Of Style ,Research Skills ,Skill Of Ideas And Finally The Skill Of Documentation Recommendation: Prepare a Guide That Summarizes the Most Prominent Proposals: Training Program to Develop Scientific Writing Skills for University Students.